شركات توظيف الأموال ودورها في الاستثمار الإسلامي : دراسة تقويمية مقاصدية - أبو العزم، رحاب
This research deals with the issue of money-investment companies in order to identify the concept and sources of their funds, and to clarify practical and scientific solutions to the problem of shutting them down in the seventies and eighties due to some unfavourable conditions and involuntary circumstances that led to their termination. Later on, the research shed a light on the development visions of these companies to keep them in business according to the latest money development and provisions of Sharia, by highlighting its role in preserving some of the Sharia objectives, and their relationship with Islamic financial engineering. The research also aimed at clarifying the Sharia adaptation of money-investing companies through its concept of cooperative financial relationship- a mutual benefit based on the investors (the company owners) and the depositors (the capital owners). The researcher discussed the concept of investment, its purposes, its interests arising from its various fields, and the role of money-investing companies in achieving the Shariah objective of protecting the money. Then, she elaborated on the most crucial challenges that these companies face, as well as the implications of their emergence and development. Furthermore, she clarified how the law, economy and Sharia can oversee these companies to protect all parties. The researcher applied the inductive and analytical method, by looking at various scientific references that discuss the topic of the research. Then, she demonstrated the information collected and analysed it, by focusing on evoking the objective of protecting the money in information linkage, and by supporting her research with a field study through conducting personal interviews with some specialists in Sharia, law and Islamic Economics. The significance of the topic of this research is evident in the fact that it provides ideas for protecting the money and investing it through money-investing companies by using savers' deposits based on modern contracts that are in line with modern developments. Among the most important findings of the research is the contribution of money-investing companies in achieving the objective of Kifayah among the Muslim community, social justice among its members, the importance of seeking help from specialists in risk management, feasibility studies, and the imperative necessity of economic integration among Muslim. Therefore, the researcher recommends the unification of the Arab currency and technological infrastructure, and the creation of a unified web for investing Muslim money.